Stability of rocky intertidal communities, in response to species removal, varies across spatial scales - Valdivia, Nelson; Lopez, Daniela N.; Fica-Rojas, Eliseo; Catalan, Alexis M.; Aguilera, Moises A.; Araya, Marjorie; Betancourtt, Claudia; Burgos-Andrade, Katherine; Carvajal-Baldeon, Thais; Escares, Valentina; Gartenstein, Simon; Grossmann, Mariana; et al. (My University, 2021)
Improving our understanding of stability across spatial scales is crucial in the current scenario of biodiversity loss. Still, most empirical studies of stability target small scales. We experimentally removed the local space-dominant species (macroalgae, barnacles, or mussels) at eight sites spanning more than 1000 km of coastline in north- and south-central Chile, and quantified the relationship between area (the number of aggregated sites) and stability in aggregate community variables (total cover) and taxonomic composition. Resistance, recovery, and invariability increased nonlinearly with area in both functional and compositional domains. Yet, the functioning of larger areas achieved a better, albeit still incomplete, recovery than composition. Compared with controls, smaller disturbed areas tended to overcompensate in terms of total cover. These effects were related to enhanced available space for recruitment (resulting from the removal of the dominant species), and to increasing beta diversity and decaying community-level spatial synchrony (resulting from increasing area). This study provides experimental evidence for the pivotal role of spatial scale in the ability of ecosystems to resist and recover from chronic disturbances. This knowledge can inform further ecosystem restoration and conservation policies.
Keywords: disturbance; habitat fragmentation; invariability-area relationship; marine protected areas; perturbation